95.0k views
3 votes
Find the value of w if the expression wx(3y² + 6y – 2) simplifies to the expression 6xy² + 12xy – 4x.

User DCZ
by
4.8k points

2 Answers

3 votes

Answer:

-7

Explanation:

User Patrick Johnmeyer
by
4.7k points
3 votes

Answer:

w = 2

Explanation:

Distribute the expression and compare like terms with the simplified version.

Given

wx(3y² + 6y - 2) ← distribute parenthesis

= 3wxy² + 6wxy - 2wx

Compare coefficients of like terms with

6xy² + 12xy - 4x

Compare xy² term, then

3w = 6 ( divide both sides by 3 )

w = 2

Compare xy term, then

6w = 12 ( divide both sides by 6 )

w = 2

Compare x term, then

- 2w = - 4 ( divide both sides by - 2 )

w = 2

Hence the required value of w is 2

User DaFunkyAlex
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.